Dosimetric characteristics of a 2D silicon diode array for stereotactic radiotherapy end-to-end patient-specific QA. (August 2020) - Bai, Long; Xiao, Qing; Wang, Qiang; Zhao, Jianling; Li, Guangjun; Bai, Sen
Abstract: The measurement accuracy of stereotactic radiotherapy (SRT) patient-specific quality assurance (QA) is challenging as small-field dosimetry contains lateral charge disequilibrium, partial blocking of the beam source, and limitations based on the detector size. The aim of this study was to investigate the dosimetric characteristics of a two-dimensional high-resolution silicon diode array for SRT end-to-end patient-specific QA. The dosimetric characteristics of the diode array, delivered to an end-to-end QA phantom, were evaluated for 6 MV, with a flattening filter (FF) and flattening filter-free (FFF), and 10 MV FFF photon beams. Dose linearity, dose rate dependence, dose-per-pulse dependence, field size dependence, angular dependence, and beam directivity were investigated for all photon beams. A total of 27 clinical plans were selected to evaluate the SRT end-to-end patient-specific QA for treatment delivery using volumetric modulated arc therapy (VMAT). For all beam qualities, the differences of dose and dose rate linearity of the diode array were below 0.7% (10–1400 MU range) and 0.6% (100–2400 MU/min range), respectively. The diodes had a decrease in sensitivity of about 4% for the 21-fold decrease in dose-per-pulse. Output factors were in good agreement for field size down to 2 × 2 cm 2 (<0.6% for both 6 MV FF and FFF beams, <1.6% for the 10 MV FFF beam), while the field size down to 0.6 × 0.6 cm 2 had an under-response (<4% for all beam qualities). Angular dependence was within ±2% and ±4%, for coplanar and non-coplanar beams, respectively. However, this was not the case for the beam direction nearly parallel to the diode array plane. Beam directivity response on both sides of the array was in excellent agreement. For the end-to-end patient-specific QA, the average gamma passing rate (GPR) with a 2%/1 mm criterion was 96.8% and the minimum value was 93.0%. There was no significant difference in the GPRs between coplanar and non-coplanar VMAT plans. The diode array, with several corrections, demonstrated good dosimetric characteristics for SRT QA. The GPRs of end-to-end patient-specific QA for non-coplanar and multiple metastases were as high as that for coplanar and single-target, and a gamma criterion of 2%/1 mm would be suitable for SRT QA when using the array. Highlights: A new high-resolution diode array was used for SRT end-to-end patient-specific QA. The dosimetric characteristics of the diode array were evaluated for SRT QA. The end-to-end testing showed high GPRs for non-coplanar and multiple metastases. Gamma criterion of 2%/1 mm would be suitable for SRT QA when using the array.